Hardwood Tree Genomics: Unlocking Woody Plant Biology - Tuskan, Gerald A.; Groover, Andrew T.; Schmutz, Jeremy; DiFazio, Stephen Paul; Myburg, Alexander; Grattapaglia, Dario; Smart, Lawrence B.; Yin, Tongming; Aury, Jean-Marc; Kremer, Antoine; Leroy, Thibault; Le Provost, Gregoire; et al. (Frontiers in Plant Science, 2018)
Woody perennial angiosperms (i.e., hardwood trees) are polyphyletic in origin and occur in most angiosperm orders. Despite their independent origins, hardwoods have physiological, anatomical, and life history traits distinct from their herbaceous relatives. New high-throughput DNA sequencing platforms have provided access to numerous woody plant genomes beyond the early reference genomes of Populus and Eucalyptus, including willow and oak with pecan and chestnut soon to follow. Genomic studies have successfully linked genes to ecological, physiological and developmental traits directly within these diverse and mostly undomesticated species. Moreover, comparative genomic approaches are providing insights into speciation events, while large-scale DNA resequencing of wild collections is identifying population-level diversity responsible for variation in key woody plant biology across and within species. Current research is focused on developing genomic prediction models for breeding, defining speciation and local adaptation, detecting somatic mutations, revealing the mechanisms of gender determination and flowering, and application of systems biology approaches to model complex regulatory networks underlying quantitative traits. Emerging technologies such as single-molecule, long range sequencing will be further leveraged as additional woody plant species and genotypes within species are sequenced, enabling a comparative (“evo-devo”) approach to understanding the unique biology of large woody plants. Resource availability, current applications, new discoveries and predicted future developments are illustrated and discussed for poplar, eucalyptus, willow, oak, chestnut and pecan.